Monatsschrift für Kriminologie und Strafrechtsreform : Journal of Criminology and Penal Reform (De Gruyter, 2012)
The Journal of Criminology and Penal Reform discusses crime and the criminal in their sociological, psychological, and psychopathological contexts. The journal also analyzes the real impact of legal measures such as punishment on society and those convicted of crimes.